PENYUSUNAN INDEKS KINERJA POLISI KEHUTANAN BALAI KONSERVASI SUMBER DAYA ALAM - Siti Asiyatun; Arzyana Sunkar; Hardjanto . (Media Konservasi, 2010)
Forest ranger is one of Natural Resources Conservation Agency (BKSDA) human resources that is assigned the job to protect and secure forests. They played very important role within The Ministry of Forestry.  As civil servant, forest ranger is evaluated using Performance Appraisal and Credit Unit.  On average, they achieved higher job rank in more than four year, which is thought to be too long. A method to enhance their performance is thus necessary.  The research objective was to formulate performance index for four levels of forest ranger's namely: junior forest ranger, forest ranger, senior forest ranger, and supervisor of forest ranger.  The research was conducted in two BKSDA, in the Provinces of Central Java and Special Region of Yogyakarta.  The performance was determined using (i) criteria and indicators, (ii) weighted indicators and (iii) performance index’s limit as requirement for promotion.  The criteria and indicators were set fixed from forest ranger’s duty, then indicator's values were defined by using Analytical Hierarchy Process’s (AHP) assessed by experts.  Performance index has five performance criteria: educational background; conducting forest protection and security operation; conducting oversight of forest products, floras and faunas circulation; professional capacity building; and carrying out complementary activities.  Each of these criteria had indicators which the amount depended on the rank of forest ranger.  Results of the Performance Index for each forest ranger’s level were 111 for junior forest ranger, 213 for forest ranger, 125 for senior forest ranger, and 72 for supervisor of forest ranger. Keywords:  forest ranger, human resources, performance index, criteria, indicator value